Safety Application and Health Work (K3) At Department of CNC Lathe Using Hazard Identification Risk Assessment and Risk Control (HIRARC) Method (Case Study of PT. Swadaya Graha) - Iwa Pramudya; Deny Andesta; Hidayat Hidayat (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Work accidents have the ability to cause the formation of every work activity. Aspects of work accidents can be caused by machines or aspects of worker negligence. The comfort of workers is highly dependent on the situation and the industrial area. One of the markers that need to be observed is occupational safety and health. So that the industry applies the K3 listed on PT Swadaya Graha which is currently still in a non-HIRARC condition as a basis for mitigation. The HIRARC procedure finds a procedure that starts to ensure the activity after which the source of the hazard is identified, risk assessment, and control over that exists and has the aim of remembering the level of risk associated with a place. From that case, the author thinks it is necessary to carry out an OHS risk assessment using the HIRARC procedure by carrying out research that aims to find out how to analyze the capabilities of hazards that can be carried out and their control on a cnc lathe machine at PT Swadaya Graha . The procedure used is the HIRARC (Hazard Identification Risk Assessment and Risk control) approach. The results of this research are that there are 5 work disaster hazard capabilities in the Ministry of CNC BUBUT. After that this research shows there is no. 1. extreme type of hazard. risk, and 1 high risk and 3 medium risk. The most common hazard abilities occur because of the lack of PPE and the undisciplined workers and not exploring work SOPs. Therefore, it is necessary to try socialization and continue to emphasize through daily safety briefings and safety signs.